Breakthrough of Difficulties and Improvement of Efficiency of Network United Front toward Taiwan in the New Era - Mao, Chunxiao (Journal of Theory and Practice in Humanities and Social Sciences, 2025)
As an important part of the new era of network united front, the network united front toward Taiwan can effectively maintain the security of network ideology, enhance the centripetal force of patriotic united front, build the greatest unity online and offline, and give full play to its advantages and exert its governance effectiveness in promoting the cross-strait peaceful reunification. It is a major issue that the united front must face in the new era. At this stage, the Chinese mainland’s network united front toward Taiwan is not only facing the external counter- pressure from the Taiwan authorities’ systematic "cognitive warfare", but also facing the internal work dilemma of its own inadequate work. This urgently needs to adapt to the development of the digital age, accurately identify changes, respond scientifically, and actively seek changes. Through technological empowerment and institutional reform, we will comprehensively promote the platform carrier and institutional mechanism innovation of the network united front toward Taiwan, build a full-domain propaganda position, forge a team of compound talents, innovate the network personnel contact mechanism, improve cross-departmental collaborative governance, give full play to the effectiveness of the new era of network united front toward Taiwan, gather the consensus of online and offline unification between the cross-strait, and consolidate the common ideological foundation for the cross-strait peaceful reunification.